Molecular characterization of ten F8 splicing mutations in RNA isolated from patient's leucocytes: assessment of in silico prediction tools accuracy. (5th February 2015) - Martorell, L.; Corrales, I.; Ramirez, L.; Parra, R.; Raya, A.; Barquinero, J.; Vidal, F.
Summary Although 8% of reported FVIII gene (F8) mutations responsible for haemophilia A (HA) affect mRNA processing, very few have been fully characterized at the mRNA level and/or systematically predicted their biological consequences by in silico analysis. This study is aimed to elucidate the effect of potential splice site mutations (PSSM) on the F8 mRNA processing, investigate its correlation with disease severity, and assess their concordance with in silico predictions. We studied the F8 mRNA from 10 HA patient's leucocytes with PSSM by RT‐PCR and compared the experimental results with those predicted in silico. The mRNA analysis could explain all the phenotypes observed and demonstrated exon skipping in six cases (c.222G>A, c.601+1delG, c.602‐11T>G, c.671‐3C>G, c.6115+9C>G and c.6116‐1G>A) and activation of cryptic splicing sites, both donor (c.1009+1G>A and c.1009+3A>C) and acceptor sites (c.266‐3delC and c.5587‐1G>A). In contrast, the in silico analysis was able to predict the score variation of most of the affected splice site, but the precise mechanism could only be correctly determined in two of the 10 mutations analysed. In addition, we have detected aberrant F8 transcripts, even in healthy controls, so this must be taken into account as they could mask the actual contribution of some PSSM. We conclude that F8 mRNA analysis using leucocytes still constitutes an excellent approach to investigate the transcriptional effects of the PSSM in HA, whereas prediction in silico is not always reliable for diagnostic decision‐making.